Fully charmed tetraquarks from LHC to FCC: natural stability from fragmentation - Francesco Giovanni Celiberto; Gabriele Gatto; Alessandro Papa (European Physical Journal C: Particles and Fields)
Abstract We investigate the inclusive production of fully charmed tetraquarks, $$T_{4c}(0^{++})$$ T 4 c ( 0 + + ) or $$T_{4c}(2^{++})$$ T 4 c ( 2 + + ) radial excitations, in high-energy proton collisions. We build our study upon the collinear fragmentation of a single parton in a variable-flavor number scheme, suited to describe the tetraquark formation mechanism from moderate to large transverse-momentum regimes. To this extent, we derive a novel set of DGLAP-evolving collinear fragmentation functions, named TQ4Q1.0 determinations. They encode initial-scale inputs corresponding to both gluon and heavy-quark fragmentation channels, defined within the context of quark-potential and spin-physics inspired models, respectively. We work within the NLL/ $$\hbox {NLO}^+$$ NLO + hybrid factorization and make use of the JETHAD numeric interface along with the symJETHAD symbolic calculation plugin. With these tools, we provide predictions for high-energy observables sensitive to $$T_{4c}$$ T 4 c plus jet emissions at center-of-mass energies ranging from 14 TeV at the LHC to the 100 TeV nominal energy of the FCC.